PENGARUH PENGHARGAAN FINANSIAL,PELATIHAN PROFESIONAL, PENGAKUAN PROFESIONAL DAN PERTIMBANGAN PASAR KERJA DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN (STUDI EMPIRIS PADA MAHASISWA JURUSAN AKUNTANSI UNIVERSITAS NEGERI MEDAN) - Kristin Marito Hutagalung; Esa Setiana (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2021)
The problem  in this research  is that Indonesia still needs a lot of accountants, but in fact students with accounting graduates show low interest in the public accounting profession. The purpose of this study was to determine the effect of financial rewards, professional training, professional recognition and labor market considerations partially and Simultaneous in choosing a career as an accountant. The population in this study were all 133 students of the 2017 Accounting Department. The sample of this study used a random sampling technique with the slovun formula, in order to obtain 55 respondents. The data analysis technique used is Multiple Linear Regression with using the SPSS 25 statistical test tool . The results of the study found empirical evidence that the variables of financial rewards, professional recognition and labor market considerations have a significant effect on career choice as an accountant. Meanwhile, Professional Recognition has no significant effect in choosing a career as an accountant.